The serpent in heaven [large type] - Harris, Charlaine (Harris, Charlaine. Gunnie Rose, 2023)
"Felicia, Lizbeth Rose's half-sister and a student at the Grigori Rasputin school in San Diego -- capital of the Holy Russian Empire -- is caught between her own secrets and powerful family struggles. As a granddaughter of Rasputin, she provides an essential service to the hemophiliac Tsar Alexei, providing him the blood transfusions that keep him alive. Felicia is treated like a nonentity at the bedside of the tsar, and at the school she's seen as a charity case with no magical ability. But when Felicia is snatched outside the school, the facts of her heritage begin to surface. Felicia turns out to be far more than the Russian-Mexican Lizbeth rescued. As Felicia's history unravels and her true abilities become known, she comes under attack from all directions. Only her courage will keep her alive."--